The Social Impact of the Global Financial Crisis in the Democratic Republic of Congo (DRC) - Kibatshi, Marcel Kamba (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2018)
The global financial and economic crisis is also causing considerable problems for the Democratic Republic of Congo in particular and sub-Saharan African countries in general. As it highlights the dysfunctions of the world economy, some believe that a reform of the international financial architecture is essential. Although the crisis was sparked by events in the US real estate market, it has spread to all regions of the world and has disastrous consequences for global trade, growth and investment. The financial crisis is a serious setback for the Democratic Republic of Congo as it comes at a time when the country is making progress in terms of both results and economic management. Since 2006, the Democratic Republic of Congo has recorded an average growth rate in real terms of more than 5% while inflation has fallen below 10%. In addition, the significant improvements in governance and the decline in the number of armed conflicts have attracted more private capital to the country. The developing countries in which the Democratic Republic of Congo is located do not, on the whole, have the same means as the industrialized nations when it comes to stimulating the economy while protecting their most vulnerable social categories. But many have made considerable efforts to mitigate the impact of the crisis. Some developing countries have intensified their reciprocal cooperation and urge closer involvement in the shaping of the rules of the world economy